ENSURING THE BEST INTERESTS OF THE CHILD IN PARENTS` CONFLICT: EXPERIENCES OF DIVORCING FAMILIES - Kairiene, Brigita; Ciuladiene, Grazina; Balionis, Agata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Divorce causes structural family changes, which require specific decisions to be made. While making any decision that might have any impact on ones‘ children welfare it is necessary to consider what is best for the children, thus children should be involved in the decision-making process. This article aims to investigate what sort of challenges parents under the divorce process face while they seek to ensure that children interests would be met.In order to conduct such an investigation, a qualitative methodology is employed. For data collection, analysis utilizes the semi-structured interview method, for the analysis of data the method of qualitative content analysis is being used. The research analysed seven couples of parents, all these couples are undergoing the divorce process and has children under 18 years of age.Research‘s data reveals that it is important for parents to meet the needs of a child, to protect the child from negative effects of the divorce, to keep the child in touch with both parents, to involve the child in the changes that are caused by the divorce. However, parents have different evaluations of children needs, on one hand, some parents do consider a child‘s opinion as of utmost importance, on the other hand, some parents believe that child‘s opinion is irrelevant. It is also has been noticed that while parents aim to ensure that child keeps in touch with both of the separated parents, conflict occurs between the parents and the child and among the parents themselves. Parents usually fight with the child over a couple of issues. Firstly, children find it inappropriate to have restricted conditions for interaction with separately living parents. Secondly, it is usually unacceptable for a child to live in a household without his father or mother. Conflicts among divorced parents occur due to different approaches to childcare as well as disputes during collaboration agreement implementation.